2011
DOI: 10.1007/s10562-011-0562-x
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic CO Oxidation on Individual (110) Domains of a Polycrystalline Pt Foil: Local Reaction Kinetics by PEEM

Abstract: The reaction kinetics of catalytic CO oxidation on individual grains of a polycrystalline Pt foil has been studied simultaneously by photoemission electron microscopy (PEEM) and mass spectroscopy (MS), in the pressure range ~10−5 mbar. By processing the video-PEEM images of ongoing catalytic reaction, the kinetic transitions were tracked for individual [110]-oriented domains. The obtained local kinetic phase diagrams were contrasted to those obtained from global MS activity measurements. These data and the obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 41 publications
5
24
0
2
Order By: Relevance
“…Usually, kinetic transitions in CO oxidation were experimentally studied under high-vacuum conditions by varying the CO/O 2 pressure ratio at constant temperature. [9,10,12] Such an experiment is illustrated for Pd foil in the right inset of Figure 2 a, at constant p O 2 ¼1.3 10 À5 mbar and T = 449 K. Similar to the case of Pt foil, [12,14,15] the global CO 2 formation rate exhibits a pronounced hysteresis upon cyclic variation of the CO partial pressure manifest by the gap between the kinetic transition t A from the high-reactivity to the lowreactivity state and the reverse transition t B . In between, the system is bistable, that is, it can be either in the high-or in the low-reactivity steady state, depending on the prehistory.…”
mentioning
confidence: 83%
“…Usually, kinetic transitions in CO oxidation were experimentally studied under high-vacuum conditions by varying the CO/O 2 pressure ratio at constant temperature. [9,10,12] Such an experiment is illustrated for Pd foil in the right inset of Figure 2 a, at constant p O 2 ¼1.3 10 À5 mbar and T = 449 K. Similar to the case of Pt foil, [12,14,15] the global CO 2 formation rate exhibits a pronounced hysteresis upon cyclic variation of the CO partial pressure manifest by the gap between the kinetic transition t A from the high-reactivity to the lowreactivity state and the reverse transition t B . In between, the system is bistable, that is, it can be either in the high-or in the low-reactivity steady state, depending on the prehistory.…”
mentioning
confidence: 83%
“…The principle of the local kinetic measurements by PEEM has been described in detail before [79] and is therefore summarized here only briefly (see also Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Our new experimental approach based on photoemission electron microscopy (PEEM) exploits the parallel imaging principle of PEEM and uses the digital analysis of in situ recorded video-PEEM files allowing thus laterally resolved kinetic measurements on a μm-scale [7, 8]. We have already applied this approach to study the local kinetics of the CO oxidation on individual grains of polycrystalline Pt [7, 9] and Pd [10] foil and to directly compare the behavior of reaction–diffusion fronts on differently oriented domains [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have sought to gain enough understanding of this system to find CO-tolerant catalysts or to engineer a Pt surface structure or morphology with a lower propensity toward CO adsorption [13][14][15][16][17]. In fact, several recent studies have found that Pt surface structural features such as particular crystallographic faces, steps, edges and defects are significant factors in its activity for methanol and CO ads oxidation [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%